OSGEP regulates islet β-cell function by modulating proinsulin translation and maintaining ER stress homeostasis in mice - Yujie Liu; Xuechun Yang; Jian Zhou; Haijun Yang; Ruimeng Yang; Peng Zhu; Rong Zhou; Tianyuan Wu; Yongchao Gao; Zhi Ye; Xi Li; Rong Liu; et al. (Nature Communications)
Abstract Proinsulin translation and folding is crucial for glucose homeostasis. However, islet β-cell control of Proinsulin translation remains incompletely understood. Here, we identify OSGEP, an enzyme responsible for t6A37 modification of tRNANNU that tunes glucose metabolism in β-cells. Global Osgep deletion causes glucose intolerance, while β-cell-specific deletion induces hyperglycemia and glucose intolerance due to impaired insulin activity. Transcriptomics and proteomics reveal activation of the unfolded protein response (UPR) and apoptosis signaling pathways in Osgep-deficient islets, linked to an increase in misfolded Proinsulin from reduced t6A37 modification. Osgep overexpression in pancreas rescues insulin secretion and mitigates diabetes in high-fat diet mice. Osgep enhances translational fidelity and alleviates UPR signaling, highlighting its potential as a therapeutic target for diabetes. Individuals carrying the C allele at rs74512655, which promotes OSGEP transcription, may show reduced susceptibility to T2DM. These findings show OSGEP is essential for islet β-cells and a potential diabetes therapy target.